PERIAPICAL CYST IN DENTAL HOSPITAL FACULTY OF DENTISTRY UNIVERSITAS INDONESIA 2018-2019 PERIOD - Evy Eida Vitria; Iwan Tofani; Maria Anneta Artha L. Malau (Fakultas Kedokteran Gigi Unjani, 2021)
A periapical cyst is a lesion often found in dental practice. It is an odontogenic cyst of inflammatory origin with an epithelial wall originating from the epithelial rests of Malassez found in the periodontal ligament. Its high prevalence compared to other types of the odontogenic cyst and the absence of recent study of its distribution and frequency based on age, gender, tooth element, position, condition of the involved tooth, and its treatment render the need for further study. A retrospective descriptive study was done using the secondary data found in the patient's medical record. The study showed some patients with periapical cysts were at the Oral and Maxillofacial Surgery Department in the 2018-2019 period. The frequency and distribution of periapical cyst are primarily found in the third decade of life (39.1%). It found more in female patients (69.6%), more often involved maxillary lateral incisive (33.3%), mostly found at the apical of involved teeth (77.8%), involved teeth condition were more often pulp necrosis (63.0%), and endodontic treatment was the more chosen treatment (22.2%). DOI : 10.54052/jhds.v1n2.p111-120